Reproducibility of the durometer and myoton devices for skin stiffness measurement in healthy subjects. Issue 3 (10th November 2018) - Dellalana, Laura E.; Chen, Fuyao; Vain, Arved; Gandelman, Jocelyn S.; Põldemaa, Mihkel; Chen, Heidi; Tkaczyk, Eric R.
Abstract: Background: Clinical assessment of skin stiffness is unreliable in many applications. The durometer, an industrial device to measure hardness, has previously been applied in scleroderma. The Myoton is a noninvasive handheld device for assessing soft tissue biomechanical parameters. Materials and Methods: We evaluated the reproducibility of both devices in six healthy subjects in the volar forearm, dorsal forearm, upper arm, shin, and calf bilaterally. The intraclass correlation coefficient (ICC) was used as a measure of reproducibility among three observers. Results: The interobserver intraclass correlation coefficient (ICC) of overall stiffness for the Myoton was 0.74 [95% confidence interval (CI) 0.45‐1.00] and 0.71 [0.39‐1.00] for the durometer. Coefficient of variation (CV) for the Myoton was 6.4% [range 1.3‐12.1] and 7.6% [range 4.4‐13.8] for the durometer. Myoton and durometer values had a Pearson correlation of 0.69. The intraobserver Myoton ICC was 0.89 [0.74‐1.00] and CV 3.1% [range 1.6‐5.0]. The 95% confidence minimal detectable change by the Myoton for a single observer is 32.4 N/m, which is 7.6% of the average subject's overall stiffness. Conclusion: The Myoton demonstrated high reproducibility, particularly in the overall stiffness parameter, and merits further investigation to assess disease progression and treatment efficacy.